Contemporary Art and Play Installations: a theoretical review (Olhar de Professor, 2025)
The article is the result of research that, based on Social Studies of Childhood in conjunction with contributions from the field of contemporary art, aims to analyze possibilities involving contemporary art and Early Childhood Education, in line with the work of Ruiz de Velasco Gálvez and Abad Molina (2011; 2019). It is a bibliographical study whose focus of analysis is the concept of game installation and its development. Based on Bardin's (2016) content analysis, the article consists of three units of analysis: 1 - Installations from the perspective of the work of Mariana Mucci, María de los Ángeles Arce and Paulina Lapolla; 2 - Installations based on work in initial teacher training; and 3 - Reverberations of play installations in academic research with children. It was thus inferred how different possibilities for working with installations can provide contexts for play and exploration, the production of games and performances by children.
Keywords: Early Childhood Education; Contemporary Art; Installations